Study on culturing Trichodema mutants - CHEN Jian-ai; WANG Wei-ming (浙江大学学报. 农业与生命科学版, 2004)
Trichodema mutants strains T5, T0803, T1010, T1003were cultured in different conditions and media, also in the presence of fungicides at 40 mg/kg (CK or procymidone+chlorothalonil, or maneb or phosethyl-Al). The pH values of media were 5, 6, 7 and 8 and hyphae were grown at temperatures of 15, 20, 25 and 30 ℃. After being cultured for 3, 4, 5, or 6 days, the strains were transferred at a lower temperature to sporulate (20 ℃). Obtained data were analyzed statistically, with the orthogonal array and ranges (R) differing dependes on the treatments (R=40.0,42.4, 48.0, 62.8, 107.0). The results indicated that the most important factor was the nature of the strain (R=107.0), while the change in temperature and time of cultivation produced the lowest effect (R=40.0). Each factor variance was significant and A3B4C2D1E3 was the optimum combined condition, in which strain T1010 grew more quickly and sporulated most.